Fungicidal Seed Coatings Exert Minor Effects on Arbuscular Mycorrhizal Fungi and Plant Nutrient Content. (1st May 2017) - Cameron, Jesse C.; Lehman, R. Michael; Sexton, Peter; Osborne, Shannon L.; Taheri, Wendy I.
Abstract : Core Ideas: Seed‐applied fungicides may inhibit arbuscular mycorrhizal fungi and plant nutrient content. Non‐target effects of seed applied fungicides may vary with crop and genotype. No negative effects of seed applied fungicides on arbuscular mycorrhizal fungi were found. Plant genotype affected arbuscular mycorrhizal fungal colonization and plant nutrient content more than fungicide. Seed‐applied fungicides have become standard on commodity crop seed to control pathogenic fungi prior to germination. However, fungicidal seed coatings containing multiple systemic ingredients targeting multiple metabolic processes may inhibit non‐target soil fungi such as obligate plant symbiotic arbuscular mycorrhizal (AM) fungi. Our experimental objectives were to: (i) determine if seed‐applied fungicidal formulations containing one or more systemic fungicides inhibit colonization of plant roots by AM fungi, plant development, or plant nutrient content during early vegetative stages of several commodity crops; (ii) identify interactions between fungicide and plant genotype. We evaluated seed‐applied fungicides labeled for use with corn ( Zea mays L.), soybean [ Glycine max (L.) Merr.], and oat ( Avena sativa L.). Three corn hybrids, three soybean varieties, and two oat varieties were raised in the greenhouse for 6 wk. Three commercial fungicides containing mixtures of locally systemic, xylem‐mobile systemic, and contact active ingredients were compared to an untreated control. Plant development, plant nutrient concentration, and percent of root colonized by AM fungi (mixed species) were measured. Fungicidal seed coatings did not significantly reduce AM root colonization or P content of any plant compared to the control. There were significant ( P < 0.05) differences among fungicides in AM fungal colonization or plant nutrient content for all three plants. Plant genotype significantly affected ( P < 0.05) AM root colonization for corn, soybean, and oat. We conclude that contemporary, seed‐applied fungicidal formulations have minimal effect on AM colonization and nutrient status of corn, soybean, and oat which were more affected by host genotype.